المقارنة بين السيرة الذاتية في الأدب العربي ونظيراتها في الأدب الغربي : A Comparison Between Autobiography in Arabic Literature And Its Counterparts in Western Literature - Dr. Muhammad Khurram Shahzad,; Dr. Abdullah Muhammad Bilal, (Al Manhal Research Journal, 2025)
This research paper presents a comparative analysis of the autobiography as a literary genre in Arabic and Western literature, examining the evolution, narrative techniques, thematic concerns, and cultural functions of autobiographical texts in both traditions. In Arabic literature, autobiographies have often served educational, ethical, and social purposes, emerging from religious and collective values. They tend to follow a chronological structure and are shaped by modesty and communal identity. In contrast, Western autobiographies focus more on individual experience, personal freedom, and psychological introspection, often employing non-linear structures and bold self-revelation. The study explores how these differences reflect broader cultural and philosophical orientations within each tradition. It further discusses representative texts—such as "Al-Ayyam" by Taha Hussein and "Confessions" by Jean-Jacques Rousseau—as primary examples of how autobiography is used to construct identity, confront society, and document personal transformation. Ultimately, the paper highlights the role of autobiography as both a mirror of the self and a window into the values of the society from which it emerges.